Analisis Pesan Dakwah pada Kisah Dua Putera Adam dalam Alquran - Muhammad Haramain (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2019)
This article study focueses on da’wah values that can be taken from two sons ofAdam story in Alquran, which by Islamic scholar interpretation conceived by story ofQabil and of Habil. This study indicates that: (a) integrity of fear and intention forsomeone is one of condition accepted the religious service of beside Allah. This Matter isdrawn in attitude had by Habil when will dedicate his him. That is why so that thesacrifice of accepted beside Allah. Differing from of Qabil, because he is dishonest inexecuting sacrifice, causing the sacrifice of the refused by Allah swt.; (b) holy head whichowned by someone will be able to have a command over him of my me of badness. Thismatter is drawn in head of Habil capable to have a command over, so that he not giveresistance when Qabil conduct badness of murder to x'self; (c) pluck Iesson of my me andsituation of God creation creature is other, including important matter. One of theexample is my me of raven which inspiring Qabil concerning procedures entomb deadbody.